The role of sexual abuse, social support and positive perspective towards school on adolescents’ psychological well-being - Hrund Jóhannesdóttir 1992- (2017)
The aim of the present study was to investigate the effect of sexual abuse and protective factors on adolescents’ psychological well-being and whether the effect differed between genders. The protective factors were in the form of social support from parents and friends, as well as having a positive perspective towards school. The present study uses data from the national survey, Youth in Iceland 2016, conducted by the Icelandic Centre for Social Research and Analysis (ICSRA). A random sample of 2039 secondary school students, was used. The results were determined using multiple regression. The results indicate that sexually abused adolescents experienced lower psychological well-being, all other variables held constant. The protective factors were connected with better psychological well-being of adolescents. However, parental support was related to higher psychological well-being for sexually abused than non-sexually abused adolescents, and positive perspective towards school was related to higher psychological well-being among non-sexually abused adolescents. Finally, the relationship between positive perspective towards school and psychological well-being was stronger for girls, than for boys. These findings indicate the importance of social support and having a positive perspective towards school on adolescents’ psychological well-being in general, and that parental support is important for sexually abused adolescents’ psychological well-being. Keywords: sexual abuse, psychological well-being, parental support, friend support, positive perspective towards school, adolescents Markmið rannsóknarinnar var að kanna tengsl kynferðisofbeldis og verndandi þátta á andlega vellíðan unglinga og hvort tengslin væru mismunandi eftir kynjum. Verndandi þættirnir voru í formi stuðnings frá foreldrum og vinum, auk þess að hafa jákvætt viðhorf til skóla. Í þessari rannsókn voru notuð gögn frá Rannsóknum og greiningu úr könnun þeirra, Ungt fólk á Íslandi 2016. Valin voru af handahófi svör 2039 grunnskólanema. Niðurstöður ...